FORMATION OF THE ARCH OF THE FOOT IN PRESCHOOL CHILDREN BY MEANS OF IMPROVING PHYSICAL TRAINING - Victoria Grigorievna Petryakova (Вестник Северо-Кавказского федерального университета, 2022)
This paper deals with the problems of flat feet in children, especially the formation of the arches of the foot in pre-school and reflected the data from our research.